Intravitreal Injection of a Rho‐Kinase Inhibitor (Fasudil) for Recent‐Onset Nonarteritic Anterior Ischemic Optic Neuropathy. (21st December 2015) - Sanjari, Nasrin; Pakravan, Mohammad; Nourinia, Ramin; Esfandiari, Hamed; Hafezi‐Moghadam, Ali; Zandi, Souska; Nakao, Shintaro; Shah‐Heidari, Mohamamad‐Hassan; Jamali, Arsia; Yaseri, Mehdi; Ahmadieh, Hamid
Abstract: This study evaluated the effects of intravitreal injection of fasudil (IVF), a Rho‐kinase inhibitor, in cases of recent‐onset nonarteritic anterior ischemic optic neuropathy (NAION). In this interventional case series, 13 eyes of 13 patients diagnosed with NAION within 14 days of onset were included. The affected eyes received a 0.025 mg/0.05 mL IVF. Functional and structural outcomes were assessed 1 and 3 months following treatment. Best corrected visual acuity (BCVA) was the main outcome measured, with mean deviation (MD) index of the VF test and peripapillary retinal nerve fiber layer thickness as secondary measures. There was a statistically significant improvement in the patients' BCVA 1 and 3 months following IVF; BCVA improved from 1.69 ± 0.55 logMAR at baseline to 0.98 ± 0.47 and 0.93 ± 0.51 logMAR at 1 and 3 months, respectively ( P = .004). The change in BCVA was not significant between month 1 and month 3 ( P = .22). Peripapillary retinal nerve fiber layer thickness decreased from 173.5 ± 29.28 µm in the baseline evaluation to 85.8 ± 8.8 µm at 1 month, and 62.9 ± 5.97 µm at 3 months ( P = .003). MD values changed from 24.60 ± 3.80 to 21.0 ± 6.10 and 20.5 ± 6.50 at 1 and 3 months, respectively ( P = .007 and .005, respectively). This pilot study suggests that IVF may be an effective treatment for patients with recent‐onset NAION. Larger studies are required to establish the therapeutic role of fasudil for NAION.